2007
DOI: 10.1300/j015v30n03_13
|View full text |Cite
|
Sign up to set email alerts
|

The Double Binds of Our Bodies

Abstract: In the dominant culture of the United States (U.S.), Asian American women contend with racial and gender-specific stereotypes that relate specifically to the images of the Asian American woman's body. Recent literature on the body image and eating disorders of Asian American women reveals that beyond the issues of body shape, weight, and traditional diagnoses, issues of racism, racially specific parts of the body, and eating disturbance beyond the traditional diagnostic categories may hold significance. A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Most conformed most closely to a cultural accommodation approach (see Leong & Lee, 2006), in which important cultural concepts are integrated into established treatment methods. Many interventions reported were consistent with recommendations made by authors who have written theoretically about treatment with Asian American women with EDs (e.g.. Ting & Hwang, 2007;Yokoyama, 2007). For example, many of the therapists employed CBT strategies in response to their clients' negative beliefs about their faces and challenged the culturally loaded thinness ethic, and some specifically attended to intemalized racism and discrimination experiences.…”
Section: Discussion and Implications For Practicesupporting
confidence: 61%
See 1 more Smart Citation
“…Most conformed most closely to a cultural accommodation approach (see Leong & Lee, 2006), in which important cultural concepts are integrated into established treatment methods. Many interventions reported were consistent with recommendations made by authors who have written theoretically about treatment with Asian American women with EDs (e.g.. Ting & Hwang, 2007;Yokoyama, 2007). For example, many of the therapists employed CBT strategies in response to their clients' negative beliefs about their faces and challenged the culturally loaded thinness ethic, and some specifically attended to intemalized racism and discrimination experiences.…”
Section: Discussion and Implications For Practicesupporting
confidence: 61%
“…A number of clients disliked their faces to the point of body dysmorphia. The inability to meet the dominant culture's definition of beauty may contribute to Asian American women's vulnerability to EDs (Yokoyama, 2007); the present study suggests that distress over facial features may be a specific risk factor for some. Smolak and Striegel-Moore (2001) stated that acculturation should be studied as a possible unique risk factor for ethnic minority women.…”
Section: Discussion and Implications For Practicementioning
confidence: 68%
“…It is widely speculated that a risk for body and eating disturbance in AA women is the impossibility of meeting Western ideals of beauty (Hall, 1995;Yokoyama, 2007), and a recent study found that AA women were impacted by internalization of Western thinness ideals in ways similar to those of the European American This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jung and Forbes (2006) asserted that EDs are not due to Western influence alone, but may be coping strategies used in the face of rapid social change, in which new economic opportunities and increasing freedoms are in conflict with traditional values. It has been hypothesized, for example, that EDs provide Asian and AA women a way of managing family and gender role distress without violating traditional gender norms (Pike & Borovoy, 2004;Yokoyama, 2007). The issues are complex, both in Asian countries and for Asian women in the U.S., and this may also be why no clear picture has emerged with regard to acculturation and disordered eating (Cummins et al, 2005;Wonderlich, Joiner, Williamson, & Crosby, 2007).…”
Section: Disordered Eating In Asian American Womenmentioning
confidence: 99%
“…Our study has a number of important counseling implications. Given Asian American women are assumed to not experience body dissatisfaction (Yokoyama, 2007), clinicians may minimize the severity of body image concerns for this population. Our results reiterate the importance of using culturally validated assessments and techniques to identify beliefs and feelings about salient features that are not captured in the present body image measures (Cummins et al, 2005).…”
Section: Practice Implicationsmentioning
confidence: 99%